Targeting SARS-CoV-2-Platelet Interactions in COVID-19 and Vaccine-Related Thrombosis - Cox, Dermot (Frontiers in Pharmacology, 2021)
It is clear that COVID-19 is more than a pneumonia and is associated with a coagulopathy and multi-organ failure. While the use of anti-coagulants does reduce the incidence of pulmonary emboli, it does not help with survival. This suggests that the coagulopathy is more likely to be platelet driven rather than thrombin driven. There is significant evidence to suggest that SARS-CoV-2 virions directly interact with platelets to trigger activation leading to thrombocytopenia and thrombosis. We propose a model of multiple interactions between SARS-CoV-2 and platelets that has many similarities to that with Staphylococcus aureus and Dengue virus. As platelet activation and thrombosis is a major factor in poor prognosis, developing therapeutics that target the SARS-CoV-2 interaction have potential in treating COVID-19 and other virus infections.